Edukasi tentang Menciptakan Inovasi dalam Industri Food and Beverage (F&B) melalui Daring - Irra Chrisyanti Dewi (Gapenas Publisher, 2022)
Towards 2030, many aspiring businessmen F&B and entrepreneurs need insight in creating and developing their business. So that community service activities through this webinar provide understanding and inspiration to F&B businesses regarding product/service innovation. In the preparation stage, the service provider collaborates with the Multivers One provider to discuss the theme agreement and the distribution of activity information. In the implementation stage, the speaker explained and continued with a questions and answer session. The final stage, speaker and providers form a whatsapp group to be able to do further coaching. The activity was because the community was attended by 50 people, they were so enthusiastic through the questions and answer session they were excited to create and develop their F&B business